UNGKAPAN PUJIAN DALAM FILM JOHN WICK KARYA DEREK KOLSTAD - Saerang, Rivan; Jansen, Frieda Th.; Manus, Jeane Angela (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â Â Â Â This research entitled â€œExpression of Compliment in The Film John Wick by Derek Kolstadâ€. The aims of this research to identify, classify, and analyze the compliment utterances and their functions in John Wick film. This research used a descriptive method. The data were collected from conversation among characters, then classified and analyzed them according to the concept of Holmes (1986). The result shows that there are five types of compliment utterances and their function applied by the characters in their dialogues. First, ability it consists of 9 compliment utterances based on compliment abilities that function to express solidarity and admiration for abilities that are real. Second, possessions consist of 4 compliment utterances based on compliments of possession that serves to express an admiration for human property that is real deserves compliment or appreciation. Third, physical appearance consist of 3 compliment utterances the function of expression a sense of attraction will fascinate the physical appearance who intends to give real compliment without the desire to mock that can establish a smooth and positive communication relationship. Fourth, Personality consist of 13 compliment utterances based on personality compliment that serves to express a sense of solidaity, admiration, appreciation of the behavior, character, or, nature of someone who can bulid oneâ€™s self-confidence. Fifth, quality consist of 6 compliment utterances based serves to express a sense of appreciation for someone good and bad qualities. This compliment phrase also serves to appreciate the actions or qualities produced by someone who can bulid oneâ€™s enthusiasm.Key words : Compliment utterances, pragmatic analysis, Film : John Wick